Thyrotropin directly affects cardiac electrophysiology and is associated with AF prevalence - Rahm, Ann-Kathrin; Wunsch, Maximilian; Seibold, Dominik; Kramp, Xenia; Schöffel, Axel; Syren, Pascal; Rivinius, Rasmus; Mages, Christine; Pfeiffer, Julia; Gampp, Heike; Caspari, Teresa; Wen, Xin; et al. (Circulation. Arrhythmia and electrophysiology, 2025)
BACKGROUND: - Although hyperthyroidism is known to increase the risk of atrial fibrillation (AF), subclinical hypothyroidism (SH) is an often-underreported condition characterized by elevated thyroid-stimulating hormone (TSH) levels and normal free triiodothyronine/free thyroxine (fT3/fT4) levels. This study aimed to clarify the association between SH and AF and to identify potential direct electrophysiological effects of TSH. - METHODS: - We retrospectively included 2311 patients diagnosed with SH between 2007 and 2020 who had an ECG within 7 days of diagnosis. Logistic regression analysis identified factors independently associated with AF in patients with SH. Effects of different TSH doses on ion channel mRNA and protein levels were analyzed in HL-1 and neonatal rat cardiomyocytes. Video analysis with MYOCYTER, patch-clamp, optical mapping, and computational modeling were used to study automaticity and action potential characteristics after TSH application. - RESULTS: - AF was documented more often with higher TSH levels (4-10 mU/L TSH: 32.1% versus >10 mU/L TSH: 44.6%; P<0.0001). Multivariable regression identified elevated TSH levels as an independent risk factor for AF. TSHR (TSH receptors) were confirmed in cardiomyocytes, and exposure to TSH led to changes in ion channel expression levels that promoted action potential prolongation. TSH also increased the beating rate in neonatal rat cardiomyocytes. We identified a TSHR-mediated cascade involving cAMP, PKA (protein kinase A), and CREB (cAMP-responsive element-binding protein) as a potential regulator of cardiomyocyte electrical remodeling leading to the proarrhythmic effects that promote the development of AF. - CONCLUSIONS: - Individuals with SH exhibit an increased prevalence of AF, which is likely in part due to a direct effect of TSH on ion channel expression in cardiomyocytes via the TSHR/cAMP/PKA pathway.